Monocytes and B cells support active replication of Chandipura virus. Issue 1 (December 2016) - Roy, Soumen; Pavitrakar, Daya; Gunjikar, Rashmi; Ayachit, Vijay; Bondre, Vijay; Sapkal, Gajanan
Abstract Background Interaction between immune system and Chandipura virus (CHPV) during different stages of its life cycle remain poorly understood. The exact route of virus entry into the blood and CNS invasion has not been clearly defined. The present study was undertaken to assess the population in PBMC that supports the growth of virus and to detect active virus replication in PBMC as well as its subsets. Methods PBMC subsets viz.: CD3+, CD14+, CD19+, CD56+ cells were separated and infected with CHPV. The infected cells were then assessed for transcription (N gene primer) and replication (NP gene primer) of CHPV by PCR. The supernatant collected from infected cells were titrated in Baby Hamster Kidney (BHK) cells to assess virus release. The cytokine and chemokine expression was quantified by flow cytometry. Results Amplification of N and NP gene was detected in CD14+ (monocyte) and CD19+ (B cell), significant increase in virus titre was also observed in these subsets. It was observed that, although the levels of IL-6 and IL-10 were elevated in CD14+ cells as compared to CD19+ cells, the differences were not significant. However the levels of TNFα and IL-8 were significantly elevated in CD14+ cells than in CD19+ cells. The levels of chemokine (CXCL9, CCL5, CCL2, CXCL10) were significantly elevated in CHPV infected PBMC as compared to uninfected cells. CCL2 and CXCL9 were significantly increased in CHPV infected CD14+ cells as compared to CD19+ cells. Conclusion CD14+ and CD19+ cells support active replication of CHPV. High viral load was detected in CD14+ cells infected with CHPV hence it might be the primary target cells for active replication of CHPV. An elevated levels of cytokines and chemokines observed in CD14+ cells may help in predicting the pathogenecity of CHPV and possible entry into the central nervous system.